Habitat-Mediated Responses of Zooplankton to Decreasing Light in Two Temperate Lakes Undergoing Long-Term Browning - Williamson, Craig E.; Overholt, Erin P.; Pilla, Rachel M.; Wilkins, Keiko W. (Frontiers in Environmental Science, 2020)
Increases in dissolved organic matter and the consequent “browning” of some lakes in recent decades are reducing water transparency to both ultraviolet and photosynthetically active radiation with important, but poorly understood ecosystem-level consequences for zooplankton grazers. The prevailing resource-based unimodal hypothesis posits that nutrients in dissolved organic matter stimulate primary production in clear-water lakes, while shading by dissolved organic matter inhibits primary production in browner lakes, with zooplankton responses following the patterns of their food resources. Support for this hypothesis derives primarily from short-term experiments, space-for-time analyses, and modeling studies. Here we use three decades of long-term monitoring data from two temperate lakes to assess zooplankton responses to changes in not only resources (chlorophyll) as drivers of change, but also light-related habitat variables (ultraviolet and photosynthetically active radiation, surface and deep-water temperatures, deep-water dissolved oxygen, and pH). The study lakes include one clear-water lake and one browner lake, both of which have experienced long-term browning. Given that zooplankton depth distribution and body size can vary with water transparency, color, and temperature, we test for responses in not only overall zooplankton abundance, but also in vertical distribution and body size. We also examine the ability of the relationship between short-term interannual variation in the driver versus response variables to predict long-term zooplankton trends. The primary responses of zooplankton were strong changes in abundance that varied with taxon and life history stage in response to habitat variables rather than food resources. Only two groups showed vertical distribution responses, and they trended toward deeper distributions with browning. There was no significant change in body size ratio. The directionality of the response of zooplankton abundance to interannual variability in the driver variables was consistent with those observed in the long-term trends for 33 of 80 comparisons (41%), though only three of those (4%) had statistically significant short-term interannual variability relationships. We conclude that habitat-related changes associated with browning in lakes have important consequences for zooplankton community structure with stronger effects in clear-water lakes than in browner lakes, and that even at the whole-lake scale short-term data are generally not adequate to predict long-term responses.